Competitive Doping Chemistry for Nickel‐Rich Layered Oxide Cathode Materials. (14th March 2022) - Guo, Yu‐Jie; Zhang, Chao‐Hui; Xin, Sen; Shi, Ji‐Lei; Wang, Wen‐Peng; Fan, Min; Chang, Yu‐Xin; He, Wei‐Huan; Wang, Enhui; Zou, Yu‐Gang; Yang, Xin'an; Meng, Fanqi; et al.
Abstract: Chemical modification of electrode materials by heteroatom dopants is crucial for improving storage performance in rechargeable batteries. Electron configurations of different dopants significantly influence the chemical interactions inbetween and the chemical bonding with the host material, yet the underlying mechanism remains unclear. We revealed competitive doping chemistry of Group IIIA elements (boron and aluminum) taking nickel‐rich cathode materials as a model. A notable difference between the atomic radii of B and Al accounts for different spatial configurations of the hybridized orbital in bonding with lattice oxygen. Density functional theory calculations reveal, Al is preferentially bonded to oxygen and vice versa, and shows a much lower diffusion barrier than B III . In the case of Al‐preoccupation, the bulk diffusion of B III is hindered. In this way, a B‐rich surface and Al‐rich bulk is formed, which helps to synergistically stabilize the structural evolution and surface chemistry of the cathode. Abstract : A model study has been performed on Group IIIA element (boron and aluminum) co‐doped high‐nickel layered oxide cathode materials to understand competitive doping chemistry. A notable difference between the atomic radii of B and Al accounts for different spatial configurations of the hybridized orbital in bonding with lattice oxygen, resulting in the formation of a B‐rich surface and an Al‐rich bulk.